Rural tourism as a rural territorial development strategy: a survey for the colombian case (2009)
Involving the use of endogenous resources, know-how and territorial identity, Rural Territorial Development (RTD) is a recent approach based on improving local productive systems competitiveness on the basis of regional inherent multifunctionality and pluriactivity. In recent years, rural tourism has become one of the strategies adopted for promotion, development and integration of local agents, leading not only to improved competitiveness but to higher income as well. Te current work presents recent trends and advances in the development of rural tourism as an income diversifcation strategy for local rural populations. It analyzes the impact of this activity in rural areas, together with its participation and importance in the tourism sector. Finally, some experiences in the development of rural tourism in Colombia and its normative and legal frame work are reviewed.